2020
DOI: 10.1007/s12325-020-01337-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Long-Term Cost-Effectiveness of Once-Weekly Semaglutide Versus Once-Daily Liraglutide for the Treatment of Type 2 Diabetes in the UK

Abstract: Introduction: Once-weekly semaglutide 1 mg is a novel glucagon-like peptide-1 receptor agonist (GLP-1 RA) for the treatment of type 2 diabetes that has demonstrated significantly greater reductions in glycated haemoglobin (HbA1c) and body weight than the GLP-1 RA once-daily liraglutide 1.2 mg in the SUSTAIN 10 trial. The present analysis aimed to evaluate the longterm cost-effectiveness of once-weekly semaglutide 1 mg versus once-daily liraglutide 1.2 mg from a UK healthcare payer perspective. Methods: Long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…The analysis was consistent with previously published cost-effectiveness analyses in the UK setting [ 10 , 11 ]. A lifetime time horizon was used, as recommended in modelling guidelines for the UK released by NICE, to ensure that all differences in long-term complications (and their impact on costs and quality of life) and mortality with once-weekly semaglutide 1 mg and empagliflozin 25 mg were captured [ 12 ].…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…The analysis was consistent with previously published cost-effectiveness analyses in the UK setting [ 10 , 11 ]. A lifetime time horizon was used, as recommended in modelling guidelines for the UK released by NICE, to ensure that all differences in long-term complications (and their impact on costs and quality of life) and mortality with once-weekly semaglutide 1 mg and empagliflozin 25 mg were captured [ 12 ].…”
Section: Methodssupporting
confidence: 89%
“…Therefore both doses of once-weekly semaglutide were considered dominant. More recently, once-weekly semaglutide 1 mg was compared with liraglutide 1.2 mg based on the SUSTAIN 10 randomized controlled trial [ 10 ]. This analysis also found that once-weekly semaglutide 1 mg was associated with improved clinical outcomes and cost savings compared with liraglutide 1.2 mg, and therefore was found to be dominant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Hansen et al (2020) identified that when two glycaemic lowering goals, HbA1c ≤ 6.5% and HbA1c < 7.0%, are reached, the cost of other subcutaneous injections of GLP-1 receptor agonists is higher than that of semaglutide. Johansen et al (2020) indicated that compared with once-daily liraglutide 1.2 mg, the life expectancy with once-weekly semaglutide 1 mg increased by 0.21 years, and the quality-adjusted life expectancy increased by 0.3 years. In terms of long-term or short-term cost-effectiveness, the choice of semaglutide to treat T2D is significantly better than that of other antihyperglycaemic drugs.…”
Section: Discussionmentioning
confidence: 99%